Implementasi Pasal 14 Peraturan Daerah Kabupaten Lampung Barat Nomor 2 Tahun 2021 tentang Pekon Wisata dalam Persepektif Siyasah Tanfidziyah - Tri Selfiana; Zuhraini; Ahmad Burhanuddin (Jurnal Hukum Lex Generalis, 2026)
This study aims to analyze the implementation of Article 14 of West Lampung Regency Regional Regulation Number 2 of 2021 concerning Tourism Villages in the management of the Batu Brak Megalithic Site in Purajaya Village from the perspective of siyāsah tanfīdhiyyah. This research employed a field research method with a descriptive qualitative approach through interviews with village officials, local communities, and tourism managers. The findings reveal that the implementation of Article 14 has not been optimal due to inadequate tourism infrastructure, insufficient public facilities, low community participation, limited awareness of tourism potential, and budget constraints at the village level. These conditions have hindered the achievement of tourism village development objectives as mandated by the regional regulation, resulting in social and economic benefits that have not been maximally realized for the community. From the perspective of siyāsah tanfīdhiyyah, the implementation of this policy has not fully reflected the principles of public welfare (maṣlaḥah) and participatory governance. Therefore, greater budget allocation, the provision of essential tourism facilities, the establishment of active tourism awareness groups and stronger partnerships among regional governments, village governments, tourism managers and local communities are required.